Representing Distant Victims: The Emergence of an Ethical Movement in Dutch Colonial Politics, 1840-1880 - Maartje Janse (BMGN: Low Countries Historical Review, 2013)
This article attempts to add to our understanding of the relations between the Netherlands and its colonies in the little researched period of 1840-1880 when this relation became politicised. This was a direct result of a new notion of citizenship that developed after the 1848 constitution was implemented: many believed that citizens had now become accountable for government policies, that is, as far as they were acquainted with the effects these had abroad. Colonial issues were among the first for which citizens developed new protest forms and demanded that public opinion should be taken more seriously by the government. This means that not only what happened in the colonies influenced the shape and structure of Dutch politics in an important formative stage, but also that sentiments usually connected to the introduction of the Ethical Policy can be traced back much earlier than is often assumed.